Rethinking Sexual and Reproductive Health and Rights for Young Women in Southern AfricaA Critical Perspective - (:unkn) unknown (My University, 2024)
This important book provides a critical examination of the sexual and reproductive health and rights (SRHR) of young women and girls in Southern Africa, examining the ways in which current policies and programmes aimed at improving SRHR often fail to reach the most marginalised populations.Addressing key regional challenges such as high rates of unintended pregnancies, unsafe abortions and high rates of HIV, the book highlights how health inequalities in the region are in fact increasing, despite the Sustainable Development Goal of ‘leaving no one behind’. It draws on theoretical analysis and empirical data gathered from studies carried out in five Southern African countries (Madagascar, Mozambique, South Africa, Zambia, and Zimbabwe), arguing that a continued focus on HIV and interventions which target health in a narrow sense often fail to understand the wider socio-economic determinants of poor sexual reproductive health, and the ways in which girls and young women are made vulnerable. Written by leading scholars in the field, this will be essential reading for students and researchers in Global Health, International Development, Women’s Studies, and all related fields.
Keywords: African Research